Petrogenesis of uranium-, thorium-, molybdenum-, and rare earth element-bearing pegmatites, skarns, and veins in the central metasedimentary belt of the Grenville Province, Ontario and Quebec. - Lentz, David Richard. (University of Ottawa (Canada), 1992)
Field examination of late-tectonic, U-, Th-, Mo-, and REE-bearing pegmatites, skarns, and veins in the southwestern Grenville Province indicates that they are spatially and temporally related. These observations lead to a renewal of the hypothesis that the deposits were related to intrusion of the pegmatites and formation of the skarns. The granitic pegmatites are related either to chemical fractionation of late-tectonic granitic plutons or mid-crustal anatectic melts with emplacement at the present structural level. This interpretation is based primarily on their discordant nature, late tectonic age, and moderately-evolved chemical composition. At the time of pegmatite emplacement the host rocks remained above 500$\sp\circ$C. Endoskarns (within pegmatite) are dominated by calc-silicate minerals (Ca pyroxene, scapolite, andradite, and titanite) and have a similar origin to the hybridized pegmatites involving metasomatic reaction of the pegmatite and skarn by either diffusion or infiltration of chemical components into the pegmatite. The exoskarns are dominantly primary with a mineralogical zonation which may be characterized as proximal to distal with relation to the pegmatite. The absence of calcite within the proximal skarn is explained in that the pegmatite-derived fluids were undersaturated in calcite resulting in dissolution. Calcite veins represent distal primary skarn. Secondary tremolite-phlogopite-sulphide replacement veins occur within the primary skarn. Fluorite-apatite-calcite veins, have inclusions and selvages of coarse-grained biotite, K-feldspar, Ca amphibole, Ca pyroxene, and titanite with occasional magnetite, sulphides, and rate-element minerals. Common minerals within the pegmatites, skarns, and veins facilitated a chemical comparison of these minerals. The colour of ferromagnesian phases, particularly Ca pyroxene and biotite/phlogopite was used in the field to describe the relative iron contents of these phases. In general, iron was highest in the minerals associated with the pegmatites, and proximal skarn; more magnesium rich in the skarns not directly associated with a pegmatite. Major- and trace-element distribution coefficients (K$\sb{\rm D})$ for coexisting phases in veins and skarns are indistinguishable, although only a few elements (Fe, Mg, Mn, and Zn) have regular distributions. In a more detailed study of the Hunt Mo skarn, four zones have been identified in the exoskarn which is, in part, consistent with observations from many other skarns in the region. The proximal zone 1 assemblage is narrow, coarse-grained (1 metre), and dominantly composed of Fe-rich Ca pyroxene, scapolite (or microcline or albite), titanite, pyrite, and molybdenite (rare quartz). The dominant skarn type, zone 2, is fine- to coarse-grained and consists of Fe-bearing Ca pyroxene, phlogopite/biotite, titanite, pyrite, and pyrrhotite, with irregular phlogopite (possibly secondary) veinlets throughout. Apatite is an accessory phase within zone 2 skarns. The third zone is composed of Ca pyroxene; phlogopite, and tremolite, and occasionally calcite and pyrite which are fine to medium grained. The fourth zone represents small veins hosted in graphite-bearing phlogopite-diopside-dolomite-calcite marble, and is dominated by fine- to medium-grained tremolite, phlogopite, calcite, pyrite $(\pm$ graphite). (Abstract shortened by UMI.)
Keywords: Geology.